From blended to online due to the COVID outbreak: the case study of a data science course. (2nd September 2021) - Vittorini, Pierpaolo; Galassi, Alessandra
ABSTRACT: Different approaches exist in delivering courses. The traditional face-to-face, the blended approach that combines the strengths of face-to-face with the application of technologies, and the online approach, which is the form of learning that takes place over the Internet. This article reports on the impact of the forced transformation of a data science course, previously provided through a blended approach, into a fully online course, due to the COVID-19 outbreak. The impact is reported in terms of the effort required by the teacher, the students' feedback and the didactic outcomes. The students' feedback and the didactic outcomes were compared with the students of the 2018/2019 academic year and between students directly involved or not in the management of the outbreak. The results show an increase in the perceived didactic quality, in the engagement and in the didactic outcomes (only the latter not statistically significant). Also, a specific tool used for the blended approach was very much appreciated by the students and we collected useful feedback for its improvement. The paper ends by summarising the main results, also discussed with colleagues, in order to consider our results alongside other experiences.